As sandálias do “profeta”: narrativas acerca do padre José Comblin e sua contribuição para a Igreja dos pobres na Paraíba, uma perspectiva das Ciências Empíricas das Religiões - Santos, Elenilson Delmiro dos (2021)
In the scope of the Empirical Sciences of Religions, which is my place of speech and starting point, it is considered that the theme of memory, narratives and modernity and their relations with religion have a privileged place of analysis. Starting from these themes, in a historical and anthropological perspective, the present thesis is aimed to comprehend the contribution of Father José Comblin (1923-2011) for the development and permanence of the Church of the Poor in Paraíba. As theoretical reference, it is adopted the studies of Maurice Halbwachs (2003) about individual and collective memory, in which it is suggested that memories should be treated as a social phenomenon whose determinant moments are defined by interpersonal relations and by the social institutions themselves. That is, giving relevance to the trainer institutions, Halbwachs understands that memory of an individual depends of his relationship with his family, his social class, with the school, with the Church, etc. From these assumptions, the research developed in the field, as well as oral testimonies conceded by some subjects (men and women) that not only knew Comblin, but also were collaborators of the formative and missionary projects of the mentioned priest became a fundamental methodological support to the research development. By end, it is demonstrated that in the Church of Paraíba, despite it had the presence of Dom José Maria Pires (1966-1995), who compromised and engaged himself in favor of the model of Church proposed by the Second Vatican Council (1962-1965), the presence of José Comblin was decisive for the Church as people of God, the Church of the Poor to consolidate itself in this State.